« La sexualité des femmes: le plaisir contraint », Nouvelles Questions Féministes, n° 3, 2010 - Guichard-Claudic, Yvonne; Andro, Armelle; Bachman, Laurence; Bajos, Nathalie; Hamel, Christelle (Nouvelles Questions Féministes, 2010)
https://shs.cairn.info/revue-nouvelles-questions-feministes-2010-3-page-4?lang=fr
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; corps; corps féminin; cours; discipline; discours dominant; europe; france; hétérosexisme; intersectionnalité; phi2030; philosophie; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; sexualité des femmes*; systèmes d'oppressions; thématiques

Célébrations! Agir et penser les féminismes - Institut de recherches et d'études féministes (FéminÉtudes, 2010)
Cette publication célèbre les 15 ans de FéminÉtudes et rend compte de la puissance réflexive des féminismes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Disponible en libre accès : https://iref.uqam.ca/feminetudes/vol-15-no-1-2010-celebrations-agir-et-penser-les-feminismes/
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; création; féminétudes; genre; histoire et politique; identités LGBTQIA2+; intersectionnalité; militance; politique; périodes historiques; québec; ressource en ligne; régions géographiques; sexualité; thématiques; travail; écriture des femmes*

The feminism and visual culture reader - Jones, Amelia (Routledge, 2010)
Feminism is one of the most important perspectives from which visual culture has been theorized and historicized over the past forty years. Challenging the notion of feminism as a unified discourse, this second edition of The Feminism and Visual Culture Reader assembles a wide array of writings that address art, film, architecture, popular culture, new media and other visual fields from a feminist perspective. The essays, 40% of which are new to the second edition, are informed by the authors’ deep attention to historical, geographical, and disciplinary contexts as well as by cutting edge concerns such as globalization, diasporic cultural shifts, developments in new media technologies, and intersectional identity politics. The Feminism and Visual Culture Reader combines classic texts with six specially commissioned pieces, all by leading feminist critics, historians, theorists, artists, and activists. Articles are grouped into thematic sections, each of which is introduced by the editor. Providing a framework within which to understand the shifts in feminist thinking in visual studies, as well as an overview of major feminist theories of the visual, this reader also explores how issues of race, class, nationality, and sexuality enter into debates about feminism in the field of the visual
Première publication: 2003
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; arts visuels et médiatiques; cours; discipline; discours dominant; fem1000; genre; har4600; identités LGBTQIA2+; interdisciplinarité; intersectionnalité; premier cycle; périodes historiques; racialisation; sexualité; systèmes d'oppressions; thématiques; théories féministes; études culturelles

Intimate Justice: A Critical Analysis of Sexual Satisfaction - McClelland, Sara I. (Social and Personality Psychology Compass, 2010)
This article elaborates an intimate justice framework to help guide research on sexual satisfaction. Using a critical historiography approach, I examine the etiology and development of the psychological construct of “satisfaction” over the last century and argue that social and political antecedents to satisfaction ratings are an essential and under-theorized aspect of research in this field. By examining what are considered to be the most influential definitions in life satisfaction research, I identify conceptual gaps, oversights, and disagreements that characterize this body of work, and specifically its theoretical treatment of inequity. Moving to the intimate domain, I argue that the field of sexual satisfaction must include theories and methods that systematically consider the role of social and sexual stigmas as antecedents to sexual satisfaction ratings. In the conclusion, building from existing social justice theories, I propose an intimate justice framework as a means to guide research that can highlight issues of entitlement and deservingness in sexual satisfaction research. This is particularly important as sexual satisfaction is increasingly used as an indicator of individual and relational well-being; however, this construct is presently limited and inadequately measured for women and men who experience limited sexual rights in the socio-political domain because of their gender and/or sexual minority status.
Keywords: approches et analyses; capacitisme; cours; discipline; intersectionnalité; justice sociale; premier cycle; psychologie; racisme; ressource en ligne; sciences humaines; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques

Ethnic, Gender, and Acculturation Influences on Sexual Behaviors - Meston, Cindy M.; Ahrold, Tierney (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
Much research has been conducted on ethnic differences in sexuality, but few studies have systematically assessed the importance of acculturation in sexual behavior. The present study assessed general differences in normative sexual practices in healthy Euro-American, Asian, and Hispanic populations, using measures of acculturation to analyze the relative effects of heritage and mainstream cultures within each group. A total of 1,419 undergraduates (67% Euro-American, 17% Hispanic, 16% Asian; 33% men, 67% women) completed questionnaires which assessed sexual experience and causal sexual behaviors. In concordance with previous studies, Asians reported more conservative levels of sexual experience and frequency of sexual behaviors, fewer lifetime partners, and later ages of sexual debut than Euro-American or Hispanic counterparts. Hispanic reported sexual experiences similar to that of Euro-Americans. There was a significant interaction between mainstream and heritage acculturation in predicting number of lifetime sexual partners in Asian women such that the relationship between heritage acculturation and casual sexual behavior was stronger at lower levels of mainstream acculturation. On the other hand, in Hispanic men, higher levels of mainstream acculturation predicted more casual sexual behavior (one-time sexual encounters and number of lifetime sexual partners) when heritage acculturation was low but less casual sexual behavior when heritage acculturation was high. These results suggest that, for sexual behavior, Hispanic men follow an “ethnogenesis” model of acculturation while Asian women follow an “assimilation” model of acculturation.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexualité; thématiques; états-unis